The involvement of the cerebellum in amyotrophic lateral sclerosis. Issue 7 (December 2013) - Prell, Tino; Grosskreutz, Julian
Abstract: Amyotrophic lateral sclerosis is a multisystemic neurodegenerative disease in which degenerative processes are not exclusively restricted to the upper and lower motor neurons. Herein, imaging and neuropathological evidence for involvement of the cerebellum, which to date is not thought to be involved in ALS, is reviewed. Evidence for involvement of the cerebellum in ALS comes from several neuropathological studies. Especially ubiquitinated forms of TDP-43 and ubiquitinated p62-positive inclusions were frequently observed. The widely used transgenic SOD1-G93A ALS mice model showed prominent cerebellar immunostaining of pERK and alterations of tau expression. Studies using advanced MRI techniques demonstrated that several cerebral areas, including the cerebellum, were recruited in order to compensate for functional motor decline. Functional MRI, voxel based morphometry, and diffusion-tensor imaging showed these cerebellar alterations as being of functional and structural nature.